2012
DOI: 10.1007/s00192-012-1887-8
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric fistula: the use of urethral plugs for the management of persistent urinary incontinence following successful repair

Abstract: A urethral plug appears to be an effective means of restoring or improving continence in women with persistent urinary incontinence following successful repair of obstetric VVF although data on long-term outcome were not available for analysis. Success rates may be lower if women have a significantly reduced bladder capacity or a new or wide urethra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The scientific community is not in consensus agreement on the definition of a successful repair. While some researchers believe success should be defined as closure of the fistula [24][25][26], others argue that dryness or continence after repair should be called success [27]. For this study, we defined success as a continent closure because the expectation of a woman with fistula is to get dry.…”
Section: Study Population and Data Collectionmentioning
confidence: 99%
“…The scientific community is not in consensus agreement on the definition of a successful repair. While some researchers believe success should be defined as closure of the fistula [24][25][26], others argue that dryness or continence after repair should be called success [27]. For this study, we defined success as a continent closure because the expectation of a woman with fistula is to get dry.…”
Section: Study Population and Data Collectionmentioning
confidence: 99%
“…Women with an unrepaired fistula may be able to have another repair attempt or be considered for a urinary diversion. For women with residual incontinence after a successful OF repair, continence may be achieved with non‐invasive techniques such as pelvic floor strengthening, bladder training or urethral plugs . Additionally, surgical procedures to alleviate stress urinary incontinence can be considered for these patients .…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic floor muscle training (PFMT) is recommended as a first line intervention in the management of women with urinary incontinence . Arguably, it might be less effective with women following vesico‐vaginal fistula because of severe damage to the continence mechanism suffered as a result of their obstructed labor . However, Dietz et al, in a study of 95 women in Addis Ababa before or shortly after vesico‐vaginal fistula repair, found that PFM anatomy and function was no more likely to be abnormal than in a general urogynaecological population.…”
Section: Persistent Urinary Dysfunctionmentioning
confidence: 99%